Tadabbur Surah Al-Fatihah di Media Sosial: Analisis Wacana Kritis pada Akun Instagram @Trvanila - Tasya Avanti Digdayani (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
The rapidly advancing digital era and changes in every aspect of life, including the dissemination of Islamic teachings and Quranic education through social media platforms. One of the most commonly used platforms is Instagram, which serves not only as a platform for sharing photos and videos but also as an educational tool for religious education. As a result, there are an increasing number of da'wah accounts, one of which is the @trvanila account, which has garnered attention for presenting surah reflections in an easy-to-understand language, accompanied by concise interpretations and motivational or reflective content related to life. This study aims to analyze how the @trvanila account packages its da'wah and motivational messages through reflections on short surahs, as well as how its linguistic and visual approaches attract audiences. Using Teun A. Van Dijk's critical discourse approach, this study examines the use of language, social interaction, and ideology contained in the da'wah content on this account. The results show that the @trvanila account uses light language, attractive visuals, and a reflective approach in conveying surah interpretations, with the public responding enthusiastically to the surah reflection content. With this strategy, religious messages can be more easily accepted by social media users, especially the younger generation. Therefore, accounts like @trvanila can serve as a relevant model for digital da'wah in line with contemporary developments..